TENACITY AND PERSISTENCE OF COPPER FUNGICIDES IN CITRUS SEEDLINGS UNDER SIMULATED RAINFALL - Fonseca, Antonio Eduardo [UNESP]; Nunes, Bruno De Moraes; Ferreira Junior, Joao Batista [UNESP] (Univ Fed Rural Semi-arido-ufersa, 2016)
The amount of fungicide that adheres to the leaf during spraying and the amount that remain on the leaf after weathering are the main factors that defines the amount of active residue on the leaf surface to effectively control plant pathogens. Thus, the objective of this work was to evaluate the tenacity and persistence of copper in citrus seedling leaves under simulated rainfall in Jaboticabal, State of Sao Paulo, Brazil. The evaluated variables were copper content, solution retention, surface tension and drop spectrum. A significant and inversely proportional linear relationship to drops < 100 mu m was found. The percentage of copper retained in leaves of citrus seedlings with copper fungicides of suspension concentrate (SC) formulations after simulated rainfall was greater than 80%. Copper fungicides of SC formulations presented the lowest surface tension, allowing greater tenacity and persistence of copper on seedlings of citrus leaves after simulated rainfall and increased contact between the drops and leaf surface.
Keywords: Chemical control; Copper retention; Surface tension